Influence of Lifestyles Related to Eating Habits in Ready Meal Consumption: comparative study between São Paulo and Rome - Siekierski, Paulette; Ponchio, Mateus Canniatti; Strehlau, Vivian Iara (Review of Business Management, 2013)
The main objective of this paper was to identify consumers’ food-related life style toward ready meals in Brazil and Italy. Our specific objectives were (1) to adapt and validate the Bae, Chae and Ryu (2010) scale and (2) to compare and associate the lifestyles to social-demographic characteristics. Consumers are working longer hours, spending more time in traffic and longing to maximize leisure time, which has been increasingly limited. As a result, they demand products and services that facilitate and support their busy lives. A survey was conducted and the research dataset was comprised of a non-probabilistic sample of 155 questionnaires from Italian consumers from Rome and 200 Brazilians from the city of São Paulo. Among the main results, it was shown that the Romans value the tradition and health dimensions more, whereas consumers from São Paulo value convenience and taste. The gender, age, number of people in the household and type of family variables are associated to the attitudes toward ready meal, as well as with its effective consumption. It is believed that these results may be relevant both for the development of new products and for the placement of products and brands active in these markets, or even to identify new market segments or understand different generations of consumers.